2003
DOI: 10.1063/1.1618735
|View full text |Cite
|
Sign up to set email alerts
|

A density functional theory investigation of 1,1-diamino-2,2-dinitroethylene dimers and crystal

Abstract: The density functional method with different basis sets was applied to the study of the highly efficient and low sensitive explosive 1,1-diamino-2,2-dinitroethylene in both gaseous dimer and its bulk state. The binding energies have been corrected for the basis set superposition errors. Four stable dimers (I, II, III, and IV) were located. The corrected binding energy of the most stable dimer IV is predicted to be −38.15 kJ/mol at the B3LYP/6-311++G** level. It was found that the structure of the most stable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…On the theoretical side, Kukilja and co workers reported shear-strain effects on decomposition mechanism, mechanical compression, electronic excitations with modifications in molecular and crystalline forms of FOX-7 with different methods [15][16][17][18][19][20][21][22][23][24][25][26][27] . A few density functional theory (DFT) calculations were performed earlier to describe the structural properties at ambient conditions, the phase stability up to 4 GPa under hydrostatic pressure, and the electronic properties and decomposition mechanism [28][29][30][31][32][33] . Recently, van der Waals (vdW) corrected DFT studies at ambient conditions were reported 34,35 , but until now there is no theoretical work to understand the vibrational and excited properties under hydrostatic pressures.…”
mentioning
confidence: 99%
“…On the theoretical side, Kukilja and co workers reported shear-strain effects on decomposition mechanism, mechanical compression, electronic excitations with modifications in molecular and crystalline forms of FOX-7 with different methods [15][16][17][18][19][20][21][22][23][24][25][26][27] . A few density functional theory (DFT) calculations were performed earlier to describe the structural properties at ambient conditions, the phase stability up to 4 GPa under hydrostatic pressure, and the electronic properties and decomposition mechanism [28][29][30][31][32][33] . Recently, van der Waals (vdW) corrected DFT studies at ambient conditions were reported 34,35 , but until now there is no theoretical work to understand the vibrational and excited properties under hydrostatic pressures.…”
mentioning
confidence: 99%
“…As could be seen from Table 3, calculated crystal lattice energy is -174.25 kJ/ mol at the B3LYP/6-31G** level. The lattice energy is larger than that of usual molecular crystals [20,21]. It indicates that the molecules in the solid are combined tightly, due to each molecule being encircled by hydrogen bonded neighbors.…”
Section: Resultsmentioning
confidence: 89%
“…The assessment of ring strain energy in ring compounds has been a topic of major interest to the organic chemist for decades [49][50][51][52][53][54][55][56][57][58]. Studies have proved that computational results of SE at the B3LYP/6-31G+(d,p) via homodesmotic process are reasonable [22,23,37,38,59] ) [61].…”
Section: Strain Energy and Heat Of Formationmentioning
confidence: 99%
“…Pyrolysis mechanism and thermal stability can be evaluated using bond dissociation energy (BDE) [20][21][22][23][24][25][46][47][48][49][50][51] which is a measure of the strength of a chemical bond. It can be defined as the enthalpy change at 298K and 1 atm in a molecule as follows:…”
Section: Computational Detailsmentioning
confidence: 99%